Effects of Implementing School-Wide Positive Behavioural Interventions and Supports on Problem Behaviour and Academic Achievement in a Canadian Elementary School. (September 2014) - Kelm, Joanna L.; McIntosh, Kent; Cooley, Sharon
Although there is much research on School-Wide Positive Behavioural Interventions and Supports (PBIS) in the United States, there is little such research in Canada. The purpose of the current study was to provide a case study example of the relation between implementing PBIS and student academic and behavioural outcomes, as well as student perceptions of the school environment. Data were collected in one school as it moved from partial to full implementation of PBIS. The results of the study indicated positive academic and behavioural outcomes for students, as well as increased perceptions of safety, understanding of school expectations, and decreased perceptions of bullying. The results of this study are discussed with implications regarding PBIS in Canada and the importance of fidelity of implementation of school-based interventions.